Clinical efficacy of local application of low-temperature plasma at treatment of chronic recurrent aphthous stomatitis - Kolenko Ю. Г.; Synko А. О. (Actual Dentistry, 2024)
Relevance. Modern studies indicate that RAS is a multifactorial disease. Although various local and systemic treatments are used to treat RAS, there is no consensus on the appropriate treatment regimens. Aim: To improve the effectiveness of treatment of patients with RAS by using low-temperature plasma. Materials and methods. The study included 80 patients: 29 men (36.25%) and 51 women (63.75%) with CRAS who sought help at the Department of Therapeutic Dentistry of the Bogomolets National Medical University. The age of the study participants was from 19 to 55 years. Eighty patients were divided into two groups. The lesions of patients in the first group (n = 55 patients) were treated with low-temperature plasma. Those in the second group (n = 25 patients) were treated with the InGaAlP diode laser. Statistical analysis was performed using the licensed MedStat 12 package and Microsoft Excel. Results: Immediately after treatment, the first group showed a decrease in contact pain of 8.01 ± 2.64, and the second group — 1.94 ± 2.77 (p = 0.000). After treatment, patients in the first group did not feel pain for 1.38 ± 1.85 days, while patients in the second group did not feel pain for 4.07 ± 3.54 days after laser therapy (p> 0.05). Complete regeneration of the afters in the first group was observed on day 5, whereas in the second group — on day 8. Conclusions. The use of low-temperature plasma in chronic recurrent aphthous stomatitis reduces the level of pain in the patient, accelerates the healing of aphthae and does not cause adverse effects.